Assessment of adnexal masses using ultrasound: a practical review - Smorgick N; Maymon R (Dove Medical Press, 2014)
Noam Smorgick, Ron Maymon Department of Obstetrics and Gynecology, Assaf HaRofeh Medical Center, Sackler School of Medicine, Tel Aviv University, Tel Aviv, Israel Abstract: Pelvic ultrasound is commonly used as part of the routine gynecologic exams, resulting in diagnosis of adnexal masses, the majority of which are functional or benign. However, due to the possible complications involving benign adnexal cysts (ie, adnexal torsion, pelvic pain) and the utmost importance of early diagnosis and treatment of ovarian cancer, the correct ultrasound diagnosis of adnexal masses is essential in clinical practice. This review will describe the typical ultrasound appearance of the common physiologic, benign, and malignant adnexal masses with the aim of aiding the clinician to reach the correct diagnosis. Keywords: adnexal cyst, Doppler, ovarian cancer